An ultra-sensitive and rapid immunosensor for the onsite detection of circulating tumor DNA in breast cancer - Bi, Yi; Lv, Xiao; Wang, Ke; Wu, Jinyu; Shi, Xiang; Zheng, Xiaodong; Lin, Xiaogang (Frontiers in Bioengineering and Biotechnology, 2024)
Breast cancer currently stands as the most prevalent form of cancer worldwide and the primary cause of cancer-related deaths among women. However, the current diagnostic methods for breast cancer exhibit several limitations, including invasiveness, high costs, and limited sensitivity and specificity. The detection of the PIK3CA-H1047R variant is of paramount importance due to its close association with tumor growth and treatment resistance. Consequently, developing a straightforward, rapid, and highly sensitive approach for detecting PIK3CA-H1047R is of utmost importance. We have been working on the development of a rapid and ultrasensitive biosensor, leveraging the alternating current (AC) electrokinetics capacitive sensing method. This biosensor involves modifying the surface of interdigital electrodes with antibodies, facilitating the antibody-antigen binding process through AC electrokinetics techniques. Our sensor strategy directly measures the interface capacitance, and the rate of change serves as a quantitative marker for event identification. Remarkably, our biosensor successfully detects the PIK3CA-H1047R antigen within a concentration range from 1 ng/mL to 1 μg/mL. In conclusion, this study proposes a fast and highly sensitive biosensor for the detection of a key breast cancer marker, PIK3CA-H1047R variant. This technology is expected to improve breast cancer diagnosis, address the limitations of current methods, and provide patients with better treatment options. This detection method offers a promising avenue for on-site and real-time sensitive detection of the PIK3CA-H1047R antigen, potentially revolutionizing breast cancer diagnosis.